Silencing of STAMP1/STEAP2 and Amplification with Apoptosis Panel Primers - Gonen, Ceren (British Journal of Healthcare and Medical Research, 2025)
Prostate cancer is the most commonly diagnosed cancer and the second leading cause of cancer mortality in men in the Western World. The effects of androgens are mediated by the androgen receptor (AR). Therefore, studies focus on identification of AR regulated genes that are also highly expressed in the prostate. STAMP family genes STAMP1/STEAP2 (Korkmaz KS., 2002) and STAMP2/STEAP4 (Korkmaz CG., 2005) are only expressed in androgen receptor positive cells, the role of AR in STAMP family gene expression is an important question. STEAP (six transmembrane epithelial antigen of prostate) (Hubert RS., 1999) is the first characterized prostate enriched six transmembrane gene, expressed in metastatic prostate cancer samples, it is tempting to speculate that STAMP/STEAP family genes may be involved in similar functions with a role for both the normal biology and pathophysiology of prostate. Using siRNA technology in LNCaP cells expressing STAMP genes per se, an apoptosis panel including pro-apoptotic and/or apoptotic molecules was assayed by RT-PCR, By this research project, prostate-specific STAMP gene family and its regulatory effects were characterized.